Risk analysis strategies in the water utility sector: an inventory of applications for better and more credible decision-making - MacGillivray, Brian H.; Hamilton, Paul D.; Strutt, J. E.; Pollard, Simon J. T. (Taylor & Francis, 2006)
Financial pressures, regulatory reform, and sectoral restructuring are requiring water utilities to move from technically inclined, risk-averse management approaches toward more commercial, business-oriented practices. Risk analysis strategies and techniques traditionally applied to public health protection are now seeing broader application for asset management, assessing competition risks, and potential threats to the security of supplies. Water utility managers have to consider these risks alongside one another, employ a range of techniques, and devise business plans that prioritize resources on the basis of risk. We present a comprehensive review of risk analysis and management strategies for application in the water utility sector at the strategic, program, and operational levels of decision making.
Keywords: decision making; risk analysis; utilities; water safety plans